A suspensão da exigibilidade do crédito tributário e de sua garantia nos crimes tributários materiais e seus efeitos na imputação penal - Saibro, Henrique da Rosa (2018)
The current work which is insert in the area of concentration Criminal System and Violence and in the research line Contemporary Legal-Criminal Systems from Postgraduate Program in Criminal Sciences at PUCRS, problematized the liability suspension of the tax credit and of its collateral in the tax consummate offenses and their effects in the criminal imputation. Besides that, it was analyzed whether the case law is sedimented (or not) regarding the topic here problematized. For this it was decided to reverse the standard of tax crimes study by starting it from the Tax Law itself, specifically in its sanctioning area. Posteriorly, it was approached the main points of contact and deviation between tax and criminal illicits and in the end, it is worked the tax criminal legal interest theories. This is the first chapter. The next chapter deals with the tax iter and the highlights of the binding summary Supreme Court opinion number 24 judgment. It is also introduced considerations about the differences between tax consummate offenses and general intent crimes. Finally, the last chapter exposes the conceptualization and the legal force from the suspensive modalities of the tax credit liability as well as their collaterals legally provided. After that, several judicial precedents are presented, preferably extracted from the Supreme Court, Federal Superior Court of Justice and Federal Circuit Court of Appeals of the Fourth Region, regarding the effects that such legal institutes causes in the criminal imputation. It is possible to affirm that some suspensive modalities of the tax credit liability causes effects in the criminal imputation, as for example the full sum deposit of the tax credit in the civil sphere, because in case of granting of the claim in the civil procedure the tax credit will be deconstituted (non-existence of crime); in the hypothesis of dismissal, the sum becomes into income to the National Treasury (extinction of punishment by the tax credit payment). If none of these hypotheses leads the accused to the conviction there is no for cause for criminal action exercise. Moreover, the caselaw framework has shown to be quite dissonant, so that it makes clear the absence of sedimentation in the courts regarding the theme worked here.